Exploring Characterization of Main Characters: Elizabeth and Darcy in Pride and Prejudice - I Gusti Agung Sri Jayantini; I Wayan Resen; Ni Made, Padmawati (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
This research pays special attention to the character analysis in the novel Pride and Prejudice, especially the two main characters, namely Elizabeth Bennet and Fitzwilliam Darcy. In accordance with theories explaining types of character and characterization, the data were carefully analyzed. The analysis focuses on how the characterization of Pride and Prejudice’s two main characters is realized. The aim of this research is to explore characterization of the main characters that is expected to contribute to the study of literature, particularly the existence of characters in the novel. Qualitative method was applied in the analysis. There were two main characters involved in the story, and many data were found to support the analysis of their characterization. Dialogues and narration in the novel were used to introduce the characterization based on three dimensions of characterization. This study found that three dimensions of characterization, including psychological, sociological, and physiological aspects of characterization could be used to make complete and vivid description of the main characters to share the values and message of the story.